Effects of Bacillus salmalaya Strain 139SI inoculation on yield and nutrients uptake of oil palm - Azri, Md Hoirul; Ismail, Salmah; Abdullah, Rosazlin (Friends Science Publishers, 2018)
Integrating the application of inorganic fertilizer with bacterial inoculants could enhance plant nutrient uptake and increase crop yield. However, their effects on the oil palm plantation industry are still less studied. Thus, this study was designed to evaluate the potential of Bacillus salmalaya strain 139SI inoculant on the enhancement of soil fertility, nutrient uptake, yield and eventually, the quality of oil produced. The results demonstrate that inoculation of B. salmalaya strain 139SI produced higher palm fresh fruit bunch (FFB) yield over the untreated. Integrating the 139SI inoculant with inorganic fertilizer resulted in more substantial FFB yield than palm received recommended inorganic fertilizer rate. Enhancement of N level in soil and nutrient uptake was also recorded in strain 139SI inoculated palm. While the number of bunches produced by palm, the oil extraction rate, and fatty acid profile shows comparable reading among all treatments. Thus, the results suggest that the application of B. salmalaya strain 139SI inoculant and inorganic fertilizer is effective for improving soil fertility, nutrient uptake and yield of oil palm.